SEARCHES OF THE PERIODS AND DEFINITION OF VARIABILITY TYPES OF NEW VARIABLE STARS TX Crv, DP Cam, IRAS 17583+5150 - Solonovich, A. P.; Bryukhanov, I. S.; Sergey, I. M. (Одеські астрономічні публікації, 2017)
Measurements of brightness of stars TX Crv, DP Cam, IRAS 17583+5150 opened in "IRAS" and "HIPPARCOS" experiments are carried out using negatives of the Odessa observatory. Proposed types of these stars: TX Crv – type ISB(?), DP Cam – type ISB, IRAS 17583+5150 – type SRB (SRC).